Purification and characterisation of starch metabolizing enzymes from streptococcus sanguis 1MC 204 - Boguo, Benjamin Liandja (My University, 2016)
An attempt has been made to purify and isolate a starch endo-hydrolase enzyme produced by Streptococcus sanguis, an organism that may be implicated in dental caries. In order to isolate the enzyme by affinity binding,& chemically modified amylopectin Was prepared, similar to the preparation of chromogenic substrate for the assay of a-arnylase, but without dye. The amylopectin was treated with 10 percent ammonium sulphate at 55°C for 45 minutes. A crude enzyme extract was prepared from concentrated culture medium and by precipitation with 60 percent ammonium sulphate. The concentrated culture medium was added to the modified amylopectin substrate and the mixture was incubate for 30 minutes at 37'C and centrifuged. The precipitate was resuspended in 20 mM bepes buffer pH 6.5 which contained 0.02 M KCI to release the enzyme from the enzyme-substrate complex. The suspension was tested for enzyme activity and the presence of proteins, More than 50 percent of the yield of the enzyme was achieved by this process, after three assays, from both crude enzyme extracts and enzyme serum samples. A 5.2 fold purification was obtained from the extraction process of the crude enzyme extract and a protective enzyme activity effect was noticed in the presence of ammonium sulphate. The analytical methods selected for the activity assay were mainly used for the activity evaluation of a-amylases and carbohydrate hydrolysing enzymes. The result showed carbohydrate interference. The isolation method proved sensitive and highly specific for the isolation of a starch metabolizing enzyme produced from Streptococcus sanguis 1MC 204. The purification of the enzyme by gel filtration and its characterization by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that this enzyme was a glycoprotein . SDS-PAGE was performed with mucin and heparin in the. presence of other. proteins as markers, and stained with the periodic acid- aldan prestained silver method. This gave one transparent-band around the phosphorylase b marker and four other more slowly running clear bands. Further, the comparison of scans of several proteins and glycoproteins with the scan of the eluted sample of the amylopectin extracted enzyme showed a similarity with the UV scan of mucin and confirmed that the enzyme was a glycoprotein. It may be further characterized by selecting methods that take into account the ambohydrate content of the protein and by eliminating the carbohydrate interference in the assays. 3
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Master of science Johannesburg. 1996
Keywords: Streptococcus mutans; Enzymes--Analysis